PENGARUH ITSAR RELATIONAL CAPABILITY DALAM KINERJA BISNIS UMKM BATIK DI PROVINSI JAWA TENGAH - Sulistyo, Heru; Nugroho, Marno; Suparman, Suparman (Borobudur Management Review, 2025)
This study aims to explore a new conceptual model that can fill the limitations of previous studies and research gaps between organizational learning centered on the concept of itsar relational capability. This type of research is explanatory research or research that is intended to explain the relationship between research variables (causality), namely adaptive learning, generative learning, itsar relational capability and business performance. The population in this study is The population in this study is Batik MSMEs in Kendal Regency, Demak Regency, Semarang Regency, Salatiga City, Semarang City and Grobogan Regency, where the business has been running for at least five years, with a sample size of 150 people. To analyze the data in this study, Structural Equation Modeling (SEM) based on SmartPLS software was used. The results of this study can be concluded as follows: adaptive learning and generative learning have been proven to increase itsar relational capability; adaptive learning, generative learning, itsar relational capability have been proven to increase business performance; Itsar relational capability will be very effective in increasing business performance if supported by adaptive learning and generative learning.